Situation Report: Czechoslovakia, 6 April 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Husak Reluctantly Reaffirms the New Course / by Vladimir Sobell Personnel Changes: Marking Time or a Small Step Forward? Polarization within the Regime Becomes More Explicit / by Vladimir Sobell Why Did They Try the Jazz Section? / by Vladimir Sobell The Trial of the Jazz Section Ends The Case of Petr Pospichal Peace and War: An Opinion Survey CC Secretary Jan Fojtik on Bloc Relations Hard-Liner Explains New Thinking in the International Communist Movement A Sharp Drop in Output during the Winter